2015
DOI: 10.1111/vop.12298
|View full text |Cite
|
Sign up to set email alerts
|

Comparative morphological evaluation of domestic animal cornea

Abstract: Differences in the distribution of CKs and AQPs in various species suggest species differences in the maintenance of structural integrity and fluid balance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
78
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(87 citation statements)
references
References 25 publications
9
78
0
Order By: Relevance
“…The anterior epitheliumstratum superficiale consisted of four to five rows of cells. This is in accordance with the findings of Nautscher et al (2016), who found that the corneal stroma in domestic animals was also the thickest layers and consisted of a uniform collagen fibril matrix. In carnivores, this epithelium consisted of six to nine cell rows; in horses 12-15 cell rows; in cattle 11-15 cells rows; in pigs and sheep 8-12 rows of squamous cells; and in the dromedary camel two to three cell rows.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The anterior epitheliumstratum superficiale consisted of four to five rows of cells. This is in accordance with the findings of Nautscher et al (2016), who found that the corneal stroma in domestic animals was also the thickest layers and consisted of a uniform collagen fibril matrix. In carnivores, this epithelium consisted of six to nine cell rows; in horses 12-15 cell rows; in cattle 11-15 cells rows; in pigs and sheep 8-12 rows of squamous cells; and in the dromedary camel two to three cell rows.…”
Section: Discussionsupporting
confidence: 93%
“…The large differences in the number of cell layers were observed in the stratum superficiale in the corneal epithelium (Meridano et al, 1998;Nautscher et al, 2016). In our study, the anterior basement membrane was weakly PAS positive in the Sulawesi bear cuscus and consisted of thin collagen fibres, while in domestic animals (Nautscher et al, 2016) the anterior basement membrane was PAS positive. The anterior epitheliumstratum superficiale consisted of four to five rows of cells.…”
Section: Discussionsupporting
confidence: 41%
See 3 more Smart Citations